Regulasi Hak Asuh Anak Pasca Perceraian: Komparasi Hukum Keluarga Islam di Indonesia, Maroko, Arab Saudi, dan Pakistan - Muhammad Rizqi Maulana; Lukman Trijaya Abadi; Wawan Irwansyah; Nia Maulina; Wiranti (CV Global Research Publication, 2026)
This study is motivated by the importance of child custody arrangements after divorce within Islamic family law, which varies across countries due to differences in fiqh schools, national legal systems, and socio-political dynamics. The aim of this research is to analyze and compare post-divorce child custody regulations in Indonesia, Morocco, Saudi Arabia, and Pakistan from the perspective of Islamic family law. The research employs a library research method with a normative juridical approach, drawing on statutory regulations, fiqh literature, and relevant academic sources. The findings indicate that all four countries generally prioritize mothers as primary custodians for children who have not reached the age of discernment, while fathers remain responsible for financial support. However, differences emerge in the age thresholds for custody, mechanisms of custody determination, and the role of courts in applying the principle of the child’s best interests. Indonesia and Morocco demonstrate more codified legal systems, Saudi Arabia has undergone reform through the 2022 Personal Status Law, while Pakistan largely relies on colonial-era legislation and judicial precedents. Overall, these legal systems reflect a gradual shift toward the principle of the best interest of the child as the central foundation in custody determination.